Future of beekeeping in Northwestern Ethiopia: Scenarios, local adaptation measures and its implications for farmers’ livelihoods - ASAMINEW TASSEW; GETACHEW ALEMAYEHU; JOHANN SÖLKNER; MARIA WURZINGER (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Tassew A, Alemayehu G, Sölkner J, Wurzinger M. 2019. Future of beekeeping in Northwestern Ethiopia: Scenarios, local adaptation measures and its implications for farmers’ livelihoods. Biodiversitas 20: 1633-1643. For this study, a participatory scenario planning approach was used to understand the driving forces, generate the plausible future scenarios of beekeeping, explore local adaptation measures and its implications for farmers’ livelihoods in Northwestern Ethiopia. Data were collected from three watersheds representing different agro-ecological zones. To identify the driving forces, different methods including key informant interviews, focus group discussions, workshops, researchers observations and literature search were applied. The data were analyzed by ranking followed by controllability, cross-impact and consistency analysis. The results show that nineteen driving forces were identified that are contributes to changes in beekeeping. Out of nineteen six most relevant and locally controllable driving forces (watershed development, deforestation, agrochemicals use, government emphasis for beekeeping development, technical support, and farmers' awareness) were selected to develop different plausible and contrasting scenarios. The three plausible and contrasting scenarios for beekeeping in 2025 are: ‘‘repressive'', ‘‘beekeeping advance'' and ‘‘beekeeping on the margins''. The results show that beekeeping significantly contributes to the livelihoods of farmers to 2025 under ‘‘beekeeping advance'' scenario. In the ‘‘beekeeping on the margins'' scenario, beekeeping has low contribution to the livelihoods of farmers. But the beekeeping is in a system of involution in ‘‘repressive'' scenario and has very low contribution to the livelihoods of farmers. The stakeholders were checked the plausibility of the scenarios and selected the ‘‘repressive’’ scenario as the worst, the ‘‘beekeeping advance’’ scenario as the best, and the ‘‘beekeeping on the margins’’ scenario as the business as usual and intervention strategies were developed to transform the current beekeeping into ‘‘beekeeping advance'' scenario. The study has shown that the participation of stakeholders in the scenario planning process provides knowledge relevant for understanding the dynamics and future scenarios of beekeeping. Hence, interventions to be made by concerned stakeholders to improve the beekeeping in the study areas need to focus on addressing the various and complex driving forces through a system wide and context-specific approach.